Health as a driving economic force - Klaus-Dirk Henke; Karl Martin (Technische Universität Berlin, Fakultät Wirtschaft und Management, 2008)
This chapter illustrates the contribution which could be made to realising the Lisbon Strategy of the European Union for growth and jobs by innovative healthcare policy favouring a preventive orientation of healthcare. The prevention and control of risk factors for chronic diseases, as well as their potential impact on the quality of human capital as a union of health and education, are discussed. Human capital refers to health and education both of the individual, and of the population as a whole
Keywords: 330; Gesundheitsvorsorge; Bildungsinvestition; Erwerbspersonenpotenzial; Alternde Bevölkerung; Deutschland; Berlin